HUKUM WARIA GANTI KELAMIN PERSPEKTIF HUKUM ISLAM DAN HUKUM PERDATA - Dimyati, Yayat (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2021)
sex change is surgery to change the gender from male to female or vice versa In this articel uses qualitative research methods using heritage research, namely research that uses ways to read books or library materials related to discussion problems. Then, the authors uses data analysis techniques with descriptive and deductive methods. How to approach using normative and phenomenological approaches. Transvestites according to language are men who are and behave like women and have feelings as women. While the shemale according to the term is the one who can not know exactly is he a man or woman, because he also has the genitals men and women. Operation change gender is operating surgically to change the gender male to female or vice versa. In Islam a man who resembles a woman is unlawful according to the hadith of a prophet which condemns a man to resemble a woman and vice versa. On the grounds that the hadith also the scholars forbid sex change for transsexual in contemporary scholars, they say that a transsexual can not be punished as person who commits immoral acts but is punished as a person who is sick and needs to be healed.